Espaço, território e paisagem: uma leitura teóricometodológica da Geografia Agrária brasileira na pós-graduação a partir dos anos 1970 - Ferreira, Darlene Aparecida de Oliveira [UNESP]; Valle, Maria Ribeiro do [UNESP]; Pessôa, Vera Lúcia Salazar; Romanatto, Maria José [UNESP]; Marafon, Gláucio José (My University, 2011)
The aim of this study was to propose a reading of theoretical and methodological geography of Brazilian agriculture in Post-Graduate Studies in Geography (PPGE's) from the Southeast, from the 1970s, trying to present a discussion of the analysis categories (space, territory, landscape, region and place) that has been unleashed over the meetings of Agrarian Geography (ENGA's) and in three meetings of the Research Groups of Agrarian Geography (2005, 2006, 2007). So, we started with the hypothesis that the relativization of scientific concepts may impair development of spatial concepts only. To accomplish our objective we carried out a survey of dissertations and theses supported in the period 1970 to 2009, in Post-Graduate in Geography and UFU UFMG (Minas Gerais), UFRJ, UFF and UERJ (Rio de Janeiro) and USP, UNESP / Rio Claro, UNESP / Presidente Prudente (Sao Paulo). The evaluation dealt with the quantitative and drew a profile of Agrarian Geography. Qualitatively, further analysis, crossing information, contextualizing the themes and especially evaluating the theoretical set referenced in the works, an indication of the possible paths followed by this branch of the Brazilian Geography for which it is observed that the references to the categories space and, more specifically the organization of space, was prioritized in the 1980s and the territory as a reference work after 1990.

O objetivo desse trabalho foi propor uma leitura teórico-metodológica da geografia agrária brasileira nos Programas de Pós-Graduação em Geografia (PPGEO’s) da Região Sudeste, a partir dos anos 1970, procurando apresentar uma discussão sobre as categorias de análise (espaço, território, paisagem, região e lugar) que vem sendo desencadeada ao longo dos Encontros de Geografia Agrária (ENGA’s) e, nos três Encontros de Grupos de Pesquisa de Geografia Agrária (2005, 2006, 2007). Assim, partiu-se da hipótese de que a relativização dos conceitos científicos pode comprometer a elaboração de conceitos apenas geográficos. Para cumprir o objetivo proposto realizou-se um levantamento de dissertações e teses, defendidas no período de 1970 a 2009, nos Programas de Pós-Graduação em Geografia da UFMG e UFU (Minas Gerais); UFRJ, UFF e UERJ (Rio de Janeiro) e USP, UNESP/Rio Claro, UNESP/Presidente Prudente (São Paulo). A avaliação realizada tratou as informações quantitativas e traçou um perfil da Geografia Agrária. De forma qualitativa, o aprofundamento da análise, cruzando as informações, contextualizando os temas e, principalmente, avaliando o conjunto teórico referenciado nos trabalhos, permitiu a indicação dos caminhos seguidos por esse ramo da Geografia brasileira para os quais se observa que nas referências às categorias o espaço e, mais precisamente a organização do espaço, foi priorizada nos anos 1980 e o território como referência dos trabalhos pós 1990.
Keywords: Space; Territory; Landscape; Graduate Programs in Geography/SE (Brazil); Espaço; Território; Paisagem; Programas de Pós-Graduação em Geografia/SE